Antiviral Effects of Oleandrin - Newman, Robert A (J Exp Pharmacol, 2020)
Over the past 15 years, investigators have reported on the utility and safety of cardiac glycosides for numerous health benefits including those as treatments for malignant disease, stroke-mediated ischemic injury and certain neurodegenerative diseases. In addition to those, there is a growing body of evidence for novel antiviral effects of selected cardiac glycoside molecules. One unique cardiac glycoside, oleandrin derived from Nerium oleander, has been reported to have antiviral activity specifically against ‘enveloped’ viruses including HIV and HTLV-1. Importantly, a recent publication has presented in vitro evidence for oleandrin’s ability to inhibit production of infectious virus particles when used for treatment prior to, as well as after infection by SARS-CoV-2/COVID-19. This review will highlight the known in vitro antiviral effects of oleandrin as well as present previously unpublished effects of this novel cardiac glycoside against Ebola virus, Cytomegalovirus, and Herpes simplex viruses.